2020
DOI: 10.18632/aging.103181
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide inhibits NF-κB and attenuates ER stress in diabetic cardiomyocyte models

Abstract: Exenatide is used to treat patients with type-2 diabetes and it also exerts cardioprotective effects. Here, we tested whether Exenatide attenuates hyperglycemia-related cardiomyocyte damage by inhibiting endoplasmic reticulum (ER) stress and the NF-κB signaling pathway. Our results demonstrated that hyperglycemia activates the NF-κB signaling pathway, eliciting ER stress. We also observed cardiomyocyte contractile dysfunction, inflammation, and cell apoptosis induced by hyperglycemia. Exenatide treatment inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Cardiomyocyte/cardiac fibroblast dysfunction is related to abnormal proliferation, apoptosis, hypertrophy, as well as inflammation and fibrosis, which may be caused by mitochondrial dysfunction and metabolic disorders. Persistent hyperglycemia can mediate hypoxic or ischemic injury, as well as elicit cardiomyocyte contractile dysfunction and the NF-κB signaling pathway activation, thus inducing ER stress [152]. GLP-1RA can help maintain a balance of energy metabolism in cardiomyocytes through activating PI3K/Akt as well as p38 MAPK pathways as well as activating Nrf-2/heme oxygenase-1 (HO-1), contributing to augmented adenosine triphosphate formation and glucose ingestion by cardiomyocytes [153][154][155].…”
Section: Improving Cardiomyocyte/cardiac Fibroblast Dysfunction By Glp-1rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyocyte/cardiac fibroblast dysfunction is related to abnormal proliferation, apoptosis, hypertrophy, as well as inflammation and fibrosis, which may be caused by mitochondrial dysfunction and metabolic disorders. Persistent hyperglycemia can mediate hypoxic or ischemic injury, as well as elicit cardiomyocyte contractile dysfunction and the NF-κB signaling pathway activation, thus inducing ER stress [152]. GLP-1RA can help maintain a balance of energy metabolism in cardiomyocytes through activating PI3K/Akt as well as p38 MAPK pathways as well as activating Nrf-2/heme oxygenase-1 (HO-1), contributing to augmented adenosine triphosphate formation and glucose ingestion by cardiomyocytes [153][154][155].…”
Section: Improving Cardiomyocyte/cardiac Fibroblast Dysfunction By Glp-1rasmentioning
confidence: 99%
“…Hyperglycemia-mediated cardiomyocyte damage is associated with inflammation. GLP-1RAs can have effects on inflammation and defending ER stress via suppressing NF-κB in diabetic cardiomyocyte models [152]. GLP-1R can also suppress cardiac hypertrophy induced by Ang II through attenuating the Nox4-histone deacetylase 4 (HDAC4) axis [162].…”
Section: Improving Cardiomyocyte/cardiac Fibroblast Dysfunction By Glp-1rasmentioning
confidence: 99%
“…Previous studies found that depression might play a role in the pathogenesis of DM in some ways: i) some environmental stressors resulted in depression and simultaneously influenced the glucose metabolism [ 31 , 32 ]; ii) depression could be an independent factor in influencing the nutrition and lifestyle behaviors of patients [ 31 , 32 ]; iii) depression had a close relationship with the disturbed gut microbiota, and the stable gut microbiota was also important to the health of patients with DM [ 33 35 ]; iv) depression could lead to the over-activation of hypothalamic-pituitary-adrenal (HPA) axis and inflammatory response to stress [ 36 , 37 ]; and the inflammation had an important role in the onset of DM [ 38 41 ]. Here, we found that these antidepressants could significantly reduce the HDRS score and HbA1c level in depressed T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the following mechanisms are activated: (1) nargirin activates glutathione (GSH), ensuring a new antioxidant defense mechanism; (2) naringin prevents the progression of hyperglycemia by increasing hepatic glycolysis and lowering hepatic gluconeogenesis; (3) nargirin shows antidiabetic effects; (4) naringin inhibits the hyperglycemia-induced NF-κB pathway [ 156 ]. The involvement of SR stress in diabetic cardiomyopathy was also demonstrated by the important results obtained in an in vitro study on H9c2 embryonic rat cardiomyoblast maintained in culture and exposed to high glucose concentrations [ 172 ]. In this study, when the cells were exposed to exenatide, a drug used in the treatment of Type 2 diabetes mellitus, the inhibition of the NF-κB signaling pathway was observed, reducing SR stress induced by hyperglycemia [ 162 ].…”
Section: Diabetic Cardiomyopathy and Bergamot Polyphenolsmentioning
confidence: 99%